Development of the myocite biobank: Cost-efficient model of public sector investigator-driven biobank for idiopathic inflammatory myositis - R Naveen; Anamika Kumari Anuja; Mohit Kumar Rai; Vikas Agarwal; Latika Gupta (Indian Journal of Rheumatology)
Background: Biobanking refers to the cryopreservation of the various biologic samples for future research. In the era of omics, biobanking has emerged as a vital process to aid research, more so for rare diseases. Aims and Methods: We describe herein the development of a biobank for idiopathic inflammatory myopathies (IIMs), a rheumatic illness with low prevalence. This study addresses the sample collection, transport, storage, maintenance, retrieval, and disposal of samples with a focus on cost-effectiveness, limitations, ethics, and legal aspects involved. Discussion: Financial constraints are juxtaposed next to a wealth of clinical data in the developing countries with a large population size and consequently high burden of rare diseases. Fine-tuning efforts toward the development of bio-archival facilities can maximize outcomes from research units in these countries. A time and cost-efficient model can be the first step toward such initiatives in the appropriate setting. Unique ethical, executive, and scientific challenges were encountered by the authors while establishing the MyoCite biobank in a resource-poor setting. The various efforts to foreclose these obstacles are discussed. Conclusion: This brief summarizes the unmet need, unique challenges, and potential solutions based on the authors' experiences gathered while setting up the MyoCite biobank for research in IIM. It also outlines the means and directions for national and global collaborations in the times ahead.